Strategi Komunikasi Pemasaran Dalam Meningkatkan Loyalitas Konsumen Pada Dinas Koperasi UMKM Provinsi Banten - Putri Handayani; Eli Apud Saepudin; April Laksana (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
This study aims to analyze the marketing communication strategies implemented by the Banten Province Cooperatives and MSMEs Office to increase consumer loyalty towards the products of its fostered MSMEs. Marketing communication strategies are a crucial aspect in creating long-term relationships between MSMEs and consumers, given the increasingly competitive market in the digital era. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation of MSMEs, consumers, and the MSME Cooperatives and MSMEs Office. The results show that the marketing communication strategies implemented include a digital-based promotional approach, improving the quality of information services, utilizing social media as a means of interaction, and holding regular product exhibition events. The implementation of these strategies can increase brand awareness, build trust, and strengthen consumers' emotional attachment to local MSME products. However, this study also found obstacles in the form of limited digital literacy among some MSMEs and limited promotional budgets. The conclusion of this study confirms that an integrated, consistent, and participatory marketing communication strategy plays a crucial role in building consumer loyalty, and needs to be supported by ongoing training programs and communication media innovation.